English for IELTS test preparation: the needs analysis - Matiini, Gharizi; Octasylva, Annuridya Rosydita Pratiwi (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2020)
The present study tried to modify IELTS Needs analysis based on the participant’ learning competence. The participant was a student with IELTS Score 4.5 and he was required to have minimum score 5.5 in order to enroll an overseas university. A skill-based analysis was used in the paper to identify the student. Questionnaire along with the placement test was conducted to get the skills that the participant needed to improve.  From the analysis, it was seen that the participant needed to improve his productive skills. Slow learning competence from the student made the instructor had to change the situation of learning process. The final result of the paper is an IELTS course preparation analysis adapted from the participant’s need. Materials, practices, assessment and Evaluation were also added in this analysis. The writer expected that such needs analysis can be employed to IELTS preparation course institution so that better learning outcomes can be achieved. DOI: 10.26905/enjourme.v4i2.4154